BS EN 13697. Chemical disinfectants and antiseptics. Quantitative non-porous surface test for the evaluation of bactericidal and yeasticidal and/or fungicidal activity of chemical disinfectants used in food, industrial, domestic and institutional areas without mechanical action. Test method and requirements without mechanical action (phase 2, step 2). (1st September 2022) - British Standards Institution,
No abstract available